Analysis of Social Media, Entrepreneurial Characteristics and Entrepreneurial Competence on MSME Performance - Vina Srimaulani; Dicky Jhoansyah; Sopyan Saori (Dinasti International Journal of Education Management And Social Science, 2025)
This study aims to determine the effect of Social Media variables, Entrepreneurial Characteristics and Entrepreneurial Competence on MSME Performance in Chicken Porridge MSME Actors in Sukabumi City. The method used in this study is an associative descriptive method with a quantitative approach. The population of this study were Micro, Small and Medium Enterprises (MSMEs) in the Chicken Porridge culinary sector in Sukabumi City. The population members studied were 166 members registered with the Sukabumi City Diskumindag in 2023, using the probability sampling method with a simple random sampling type. This study uses IBM SPSS Version 25 software as a data analysis tool. The results of the study indicate that all hypotheses are accepted, which means there is a positive and significant influence between Social Media on MSME Performance with a t-value of 2.994> t table 1.658 and a significance value of 0.003 <0.05, Entrepreneurial Characteristics on MSME Performance with a t-value of 2.706> t table 1.658 and a significance value of 0.008 <0.05, and between Entrepreneurial Competence on MSME Performance with a t-value of 3.434> t table 1.658 and a significance value of 0.001 <0.05. Thus, Social Media, Entrepreneurial Characteristics and Entrepreneurial Competence affect MSME Performance.